Strategy Management in Improving the Quality of Learning for Residents Learning Pkbm Al Ghoutsillah Batu Tunau Village - Abduh, Muhamad; Yahyadin, Muhammad; Ahdar, Muhammad; Suriansyah, Ahmad; Purwanti, Ratna (Journal of English Language and Education, 2025)
This study aims to analyze the implementation of strategic management in improving the quality of learning at PKBM Al Ghoutsillah, Batu Tunau Village. The focus includes planning, implementation, and evaluation of strategies carried out by PKBM administrators to address educational challenges faced by learners, particularly school dropouts. The research method used is qualitative descriptive, utilizing observation, in-depth interviews, and documentation. The results show that the strategic management process includes formulating adaptive visions and missions, designing learning programs based on learners’ needs, and conducting regular evaluations to ensure quality improvement. In conclusion, the effective application of strategic management significantly contributes to increased motivation, participation, and learning outcomes of PKBM learners.